1996
DOI: 10.1074/jbc.271.16.9704
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Peptide Corresponding to the Rab4 Hypervariable Carboxyl-terminal Domain Inhibits Insulin Action on Glucose Transport in Rat Adipocytes

Abstract: The present study was conducted to examine the involvement of Rab4, a low molecular weight GTP-binding protein, in the action of insulin on glucose transport. A synthetic peptide corresponding to the Rab4 hypervariable carboxyl-terminal domain, Rab4-(191-210), was successfully transferred into rat adipocytes by electroporation and inhibited insulin-stimulated glucose transport by about 50% without affecting the basal transport activity. In contrast, synthetic peptides corresponding to the Rab3C and Rab3D carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 45 publications
4
47
1
Order By: Relevance
“…5), similar to that of the inhibition by wortmannin of glucose transport activity (29,30). These results, together with our previous observations (16), provide further evidence that activation of Rab4 may be one of possible mechanism(s) by which insulin promotes GLUT4 translocation.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…5), similar to that of the inhibition by wortmannin of glucose transport activity (29,30). These results, together with our previous observations (16), provide further evidence that activation of Rab4 may be one of possible mechanism(s) by which insulin promotes GLUT4 translocation.…”
Section: Discussionsupporting
confidence: 73%
“…In a previous report, to elucidate the physiological significance of Rab4 in the insulin action, we incorporated into rat adipocytes a synthetic peptide corresponding to the Rab4 hypervariable carboxyl-terminal domain and showed that the peptide specifically inhibited glucose transport and GLUT4 translocation stimulated by insulin or GTP␥S 1 (16), providing evidence that Rab4 plays a critical role in the insulin-induced GLUT4 translocation. It remains to be clarified, however, whether or not Rab4 lies downstream of the insulin receptor and functions as a signaling component of insulin activation of glucose transport.…”
mentioning
confidence: 99%
“…However, it has been suggested that the mode of action of GTP␥S may differ from that observed with insulin (38). Hence, it was of interest to determine if the VAMP2 inhibitory effect on GLUT4 translocation was a general effect or somewhat specific to insulindependent movement.…”
Section: Table I Sequence Comparison Of the N Termini Of Different V-mentioning
confidence: 99%
“…In mammalian cells, there are more than 50 different rab GTPases described that are localized to different subcellular compartments with distinct regulatory functions mediating specific membrane traffic steps (for reviews see References [159][160][161][162]). Among this large family, Rab4 has been shown to associate with GLUT4 containing vesicles and implicated in insulin action in adipocytes [163,164]. Rab4 appears to undergo an insulin-stimulated redistribution from GLUT4 vesicles to the cytosol, where it associates with the GDP-dissociation inhibitor GDI-I [153,165].…”
Section: Other Modulators Of Glut4 Traffickingmentioning
confidence: 99%